PENERAPAN E-MODUL PEMBELAJARAN BERBASIS PENDIDIKAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS X SMAN 2 SUTERA - Dwita Elfri Mayani (Jurnal Edukasi dan Penelitian Matematika, 2022)
The success of a learner in understanding concepts of learning is typically determined by the learning results they achieve. Despite the high final term value assessment of mathematics class X SMAN 2 Sutera 2020/2021, the school is still concerned about the low level of student achievement. One manner to address the problem is to use the realistic mathematical learning module of the mathematical learning process. This study is aimed at documenting the outcomes of students who learned mathematics through realistic educational modules at SMAN 2 Sutera. The type of research being conducted is a pre-experiment designed for the one shot case study. The student is a member of the 2020/2021 class at the X science SMA N 2 Sutera. The instrument used is a mathematical check that may be defined in terms of matter of description, and the data is analyzed by the test sample t. Analysis of the data shows that H0 is rejected is can be concluded that an e-learning module based on realistic mathematical education affect the results that learn with a facts-based learning module are batter than those of prveious learning. Keywords: E-modul, Realistic Math Education, Results from Studying Mathematics